The Oxford dictionary of art - Chilvers, Ian (Oxford Oxford University Press, 2004)
"The Oxford Dictionary of Art is the unrivalled one-volume guide to the art of the Western world. It provides a careful balance of fact and critical appraisal, ranging across painting, sculpture, and the graphic arts from classical times to the present. Almost 3,500 entries provide the reader with readily accessible information,written in succinct and readable prose, about styles, techniques, collections, artists, and critics. Ideal for students, picture researchers, and art lovers in general."--Jacket.
Includes index.
Keywords: Art -- Dictionaries; Artists -- Biography -- Dictionaries; Art -- Dictionnaires anglais; Artistes -- Biography -- Dictionnaires anglais